2021
DOI: 10.1080/10717544.2021.1905751
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib self-assembled nanoparticles decorated with hyaluronic acid for targeted treatment of tumors to overcome multidrug resistance

Abstract: Multidrug resistance (MDR) and lack of targeting specificity are the main reasons why traditional drug therapies fail and produce toxic side effects in cancer chemotherapy. In order to increase targeting specificity and maximize therapeutic efficacy, new intelligent drug delivery systems are needed. In this study, we prepared the hyaluronic acid (HA) conjugated dasatinib (DAS) and D-α-tocopherol acid polyethylene glycolsuccinate (TPGS) copolymer nanoparticles (THD-NPs). The water solubility of the hydrophobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…As shown in Figure 6A and B , the accumulation of DAS and OLA in the HDO-NPs group was higher than that in the free DAS + OLA group at each time point, owing to the introduction of hyaluronic acid, which could be better taken up by tumor cells and increase drug endocytosis. 38 Meanwhile, the drug accumulations in the HA blocking group were lower than that in the HDO-NPs group, which also reflected the above conjecture, further showing that the targeting of HA can enhance the accumulation of drugs in cells.
Figure 6 The accumulation of ( A ) DAS and ( B ) OLA in MDA-MB-231 cells incubated with DAS + OLA, HA + HDO-NPs and HDO-NPs for different times.
…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…As shown in Figure 6A and B , the accumulation of DAS and OLA in the HDO-NPs group was higher than that in the free DAS + OLA group at each time point, owing to the introduction of hyaluronic acid, which could be better taken up by tumor cells and increase drug endocytosis. 38 Meanwhile, the drug accumulations in the HA blocking group were lower than that in the HDO-NPs group, which also reflected the above conjecture, further showing that the targeting of HA can enhance the accumulation of drugs in cells.
Figure 6 The accumulation of ( A ) DAS and ( B ) OLA in MDA-MB-231 cells incubated with DAS + OLA, HA + HDO-NPs and HDO-NPs for different times.
…”
Section: Resultssupporting
confidence: 52%
“…HDO-NPs were hydrolyzed by strong alkaline hydrolysis to determine the drug loading and encapsulation efficiency of DAS and OLA. 37 , 38 In short, 4 mg HDO-NPs were dissolved in 1 mL deionized water, 100 μL NaOH (1 mol/L) was added for 0.5 h, and then 100 μL HCl (1 mol/L) was added for neutralization. Subsequently, 3 mL methanol was added to dissolve the cracked DAS and OLA, which were mixed evenly and centrifuged (5000 rpm, 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure A, B, the fluorescence intensity of ICG-Osi increased in a dose- and pH-dependent manner. The strongest fluorescence intensity was detected at a pH level of 5.5, similar to that of the tumor microenvironment . These results suggested that ICG-Osi could therefore be used for in vivo tumor tracking.…”
Section: Resultsmentioning
confidence: 99%
“…The natural polymers used for gene-based therapy include chitosan, atelocollagen, folate (FA), HA, and gelatin, and are biocompatible, biodegradable, and generally nontoxic, even at high concentrations. Chitosan has been successfully used in gene delivery systems [155][156][157]. Novel chitosan nanoparticles were developed to deliver functional miRNA mimics to macrophages through regulating ABCA1 expression and cholesterol efflux to target atherosclerotic lesions [158].…”
Section: Polymer-based Nanoparticlesmentioning
confidence: 99%